4. Determine os produtos:
a) ( 8xy - 2 ) ( 8xy + 2 )
b) (1 + m² n³ ) ( 1 - m² n³)
Soluções para a tarefa
Respondido por
26
Oiii
a)
![\boxed{(8xy - 2).(8xy + 2) = (8xy)^{2} - 2^{2} = \boxed{ (8xy)^{2} - 4}} \boxed{(8xy - 2).(8xy + 2) = (8xy)^{2} - 2^{2} = \boxed{ (8xy)^{2} - 4}}](https://tex.z-dn.net/?f=%5Cboxed%7B%288xy+-+2%29.%288xy+%2B+2%29+%3D+%288xy%29%5E%7B2%7D+-+2%5E%7B2%7D+%3D+%5Cboxed%7B+%288xy%29%5E%7B2%7D+-+4%7D%7D)
b)
![(1 + m^{2} n^{3} ) ( 1 - m^{2} n^{2}) =
1-(m^{2}n^{3})^{2}
1-(m^{2})^{2}(n^{3})^{2}
1 - m^4(n^{3})^{2}
\boxed{1-m^{4}n^{6}} (1 + m^{2} n^{3} ) ( 1 - m^{2} n^{2}) =
1-(m^{2}n^{3})^{2}
1-(m^{2})^{2}(n^{3})^{2}
1 - m^4(n^{3})^{2}
\boxed{1-m^{4}n^{6}}](https://tex.z-dn.net/?f=%281+%2B+m%5E%7B2%7D+n%5E%7B3%7D+%29+%28+1+-+m%5E%7B2%7D+n%5E%7B2%7D%29+%3D%0A%0A+1-%28m%5E%7B2%7Dn%5E%7B3%7D%29%5E%7B2%7D%0A%0A1-%28m%5E%7B2%7D%29%5E%7B2%7D%28n%5E%7B3%7D%29%5E%7B2%7D%0A%0A1+-+m%5E4%28n%5E%7B3%7D%29%5E%7B2%7D%0A%0A%5Cboxed%7B1-m%5E%7B4%7Dn%5E%7B6%7D%7D)
a)
b)
Respondido por
14
Oi Nina
a) (8xy - 2)*(8xy + 2) = 64x²y² - 4
b) (1 + m²n³)*(1 - m²n³) = 1 - m^4n^6)
.
a) (8xy - 2)*(8xy + 2) = 64x²y² - 4
b) (1 + m²n³)*(1 - m²n³) = 1 - m^4n^6)
.
Perguntas interessantes
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás